Analysis of Short Circuits in San Juan - Brignardello, María; Andrieu, Jimena (Instituto de Investigaciones Socioeconómicas, 2020)
In the province of San Juan, Argentina, a series of trade fairs that promote a type of exchange that is presented outside the dominant circuits of trading has been launched, proposing a type of short circuits of marketing. In this article we propose to know which are those dimensions, agents and institutions that allow the fairs of the departments of Calingasta and Jáchal to be maintained over time and which forms they acquire in their daily practice. The methodological strategy proposed is qualitative and involved conducting interviews and analyzing written documents. In these associative frames the State appears, from decentralized spaces, and other non-state institutions, that provide support for the organization, provide access to financing sources and provide technical resources, which were essential to start and continue these fairs. This concludes that these associative networks, although mobile, are essential elements to understand how these short circuits of marketing are maintained over time (and how they change).